Anxiety in Speaking: What Factors and How to Overcome - Ramli; Fitriawati; Nirmala, Anjelina (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2024)
This study aims to investigate students' speaking anxiety in English classes in the second semester of Universitas Borneo Tarakan. Specifically, this study examines the factors that influence students' speaking anxiety and strategies to minimize it based on what the students have experienced. Thirty-eight students were selected as research subjects using a specialized sampling method. The researchers used a descriptive qualitative method with a phenomenological approach by conducting interviews, questionnaires, and observations with students who have anxiety in speaking English. The results showed two factors, including internal factors, i.e., discouragement (feeling shy), lack of confidence, and fear of making mistakes, and external factors (limited vocabulary and friends/classmates). And there are two strategies shown in this study (preparation and relaxation). The conclusion of this study is that speaking anxiety can occur and hinder students' speaking performance. Therefore, strategies are needed to do so in order to make it easier for students to speak.